Developing Vlog (Video Blog) Mediated Supplementary Reading Materials - tri wahyuni (Language-Edu, 2020)
Nearly vocational students have difficulty understanding reading as a foreign language learner. This is because this book is not interesting in both hard and soft forms, so this study discusses additional information as a complement to clarify what they want to learn (and for reference, students) about media technology and their attitudes toward it. use in teaching and learning. English is a foreign language (FLT / L) in vocational schools but very necessary in their daily lives, Next is students having difficulty understanding English reading so the teacher tries to make students who really like the development of technology and they prefer to read books through gadgets and they prefer to see from reading because the teacher is required to be able to convey the material to be discussed.  While the model used by researchers is (Grabe 2008) top-down models such as the importance of the background knowledge of the reader. By combining students' needs for their insights before they read the text, they get a general picture of what they will read in the form of vlogs. With vlogs in addition to teaching reading, it will overcome the time constraints of class XI students. Based on the legal basis of the Vocational Education Law No. 20 of 2003 and the needs of Class XI students from the results of the questionnaire they had filled out and interviewed with several students, their problems would be helped by using vlogs. Therefore, as a teacher, I try to make students easy to understand after seeing a video on a blog (VLOG) and proceed with understanding the readings they read easily.  Vlogging is very similar to blogging, where people post information or ideas on a website. The main difference is that media is video, not text. Many people consider vlogging as a video blog. This allows users to share thoughts, feelings, and information with a visual platform. How to put text-reading supplements on Vlogs, Vlogs are something that are familiar to students today, especially vocational school students. An easily managed vlog that can provide a place for English students where they can receive additional material in understanding reading, reflecting, commenting, asking questions, acting inside and outside the classroom in an authentic environment. Keywords:   Vlog (Video Blog), Mediated Supplementary